Preparation for Endurance Competitions at Altitude: Physiological, Psychological, Dietary and Coaching Aspects. A Narrative Review - Burtscher, Martin; Niedermeier, Martin; Burtscher, Johannes; Pesta, Dominik; Suchy, Jiri; Strasser, Barbara (Frontiers in Physiology, 2018)
It was the Summer Olympic Games 1968 held in Mexico City (2,300 m) that required scientists and coaches to cope with the expected decline of performance in endurance athletes and to establish optimal preparation programs for competing at altitude. From that period until now many different recommendations for altitude acclimatization in advance of an altitude competition were proposed, ranging from several hours to several weeks. Those recommendations are mostly based on the separate consideration of the physiology of acclimatization, psychological issues, performance changes, logistical or individual aspects, but there is no review considering all these aspects in their entirety. Therefore, the present work primarily focusses on the period of altitude sojourn prior to the competition at altitude based on physiological and psychological aspects complemented by nutritional and sports practical considerations.